2022
DOI: 10.21608/ijthm.2022.270109
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes of Women Empowerment in Egyptian Travel Agencies: Perceived Fairness as a Mediator

Abstract: Women in tourism are still concentrated in the lower-status and lowerpaid jobs. Yet the integration of women in the labor market is still in process, as gender inequality at the workplace is still found. Therefore, the current paper aims to investigate the predictors and outcomes of women empowerment in Egyptian travel agencies. Furthermore, it examines the mediating effect of perceived fairness in the relationship between women empowerment and employee outcomes. PLS-SEM was employed to analyze the perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…As evidenced in figure (3). The result of Zaki and Al-Romeedy (2018) (31) were congruent with the current study findings who exploring the influence of toxic leader ship on job security and found that the job security correlated negatively with toxic leader ship dimensions. Also, Abou-Ramadan and Eid (2020) (32) and Özkan.…”
Section: Nursing Staff' Perception Of Job Securitysupporting
confidence: 90%
“…As evidenced in figure (3). The result of Zaki and Al-Romeedy (2018) (31) were congruent with the current study findings who exploring the influence of toxic leader ship on job security and found that the job security correlated negatively with toxic leader ship dimensions. Also, Abou-Ramadan and Eid (2020) (32) and Özkan.…”
Section: Nursing Staff' Perception Of Job Securitysupporting
confidence: 90%
“…Therefore, it is concluded from this finding that the scale have high levels of internal consistency and are considered to be very reliable, where Cronbach's Alpha values are < .746. Thus, all the constructs and variables used in this study are based on well-established instruments with high reliability scores, and the internal consistency of each construct is substantiated to be very good (Zaki et al, 2022).…”
Section: Results and Discussion Of The Study Demographic And Other Wo...mentioning
confidence: 79%